2020
DOI: 10.3390/ijerph17186724
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of a Calling: The Mediating Role of Harmonious and Obsessive Passions in the Relationship between a Calling, Workaholism, and Work Engagement

Abstract: Even though research on perceiving a calling has been growing, our understanding of its double-edged sword effects and psychological mechanisms remain unclear, especially in terms of work engagement and workaholism. Based on the heavy working investment (HWI) and dualistic model of passion (DMP) theories, we established a dual-path structural model to examine the effects of callings on work engagement and workaholism through two types of passion: harmonious (HP) and obsessive (OP) passions. Our results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Since Oates [1] first defined the term workaholism as an uncontrollable need or compulsion to work, a number of studies have examined the negative consequences of the concept [2][3][4] and predictors thereof [5,6]. Although these studies have contributed meaningfully to the literature, most have focused on the domain of self-perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Since Oates [1] first defined the term workaholism as an uncontrollable need or compulsion to work, a number of studies have examined the negative consequences of the concept [2][3][4] and predictors thereof [5,6]. Although these studies have contributed meaningfully to the literature, most have focused on the domain of self-perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Research has linked calling to outcomes such as perceived well-being, meaningfulness, fulfilment, and work engagement (for a review, see Dik & Duffy, 2009. That said, vocational calling may also be a doubleedged sword, with potential links to workaholism, burnout, and organizational exploitation (Choi et al, 2020;Keller et al, 2016). When situated in our immoral economy, the risks of valorizing excessive work and productivity may be heightened for those who are lucky enough to find meaningful work.…”
Section: Christian Hegemonymentioning
confidence: 99%
“…Over the past decade, hundreds of empirical research studies on a calling have been published and have consistently shown that workers with a calling are a benefit to both their organizations and the individuals within them (Bunderson and Thompson, 2009; Cardador et al ., 2011; Choi et al ., 2020). A calling has also been shown to be related to positive work outcomes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As corporate counselors conduct a coaching program, it is essential to let workers perceive and understand the CSR of their organization. Considering that CSR has elicited various positive work-related outcomes (Glavas and Kelley, 2014; Choi et al ., 2020; Turker, 2009), CSR can be expected to play an important role in boosting the synergistic effects among workers with a calling. In addition, career counselors who are working with job seekers with a calling could recommend occupations and organizations in which job seekers' calling could effectively be expressed to improve the meaningfulness of their work and help them live up to their calling (Duffy et al , 2018).…”
Section: Practical Implicationsmentioning
confidence: 99%